The influence of perceived formative assessment on the learning autonomy of medical students: the chain mediating role of psychological empowerment and positive academic emotions - Wang, Jiali; Zhou, Guorun; Guo, Juntang; Sun, Xiaodong; Sun, Lin (Frontiers in Public Health, 2024)
Medical students' autonomous learning is a cornerstone of their educational journey. Formative evaluation is defined as a process to enhance learning and improve academic performance, and the key to the effectiveness of formative evaluation is the students' perceptions of it. The present study investigates the impacts of perceived formative evaluation on the learning autonomy of medical students, explores the chain mediating role of psychological empowerment and positive academic emotions, and offers strategies for facilitating medical students' autonomous learning. A crosssectional investigation was conducted using convenience sampling of 713 medical students (mean age 19.72±1.18years; 207 males and 506 females; the proportion of participants is 93.69%) in Shandong Second Medical University. Perceived formative evaluation was evaluated using selfdesigned questionnaire of Perception of Formative Evaluation for medical students, learning autonomy using Autonomy in Learning Rating Scale for College Students, positive academic emotions using General Academic Emotion Questionnaire for College Students, and psychological empowerment of medical students using Chinese version of Psychological Empowerment Scale (PES). Data were analyzed with descriptive statistics, Pearson's correlation, multiple regression, and mediation analysis using SPSS26.0 program and PROCESS3.1. There were significant positive correlations among perceived formative evaluation, positive academic emotions, psychological empowerment and learning autonomy of medical students. Mediation effect analysis revealed that perceived formative evaluation has positive influences on learning autonomy of medical students through both psychological empowerment and the chain of psychological empowerment and positive academic emotions. The total mediation effect size was 70%. Perceived formative evaluation was found to positively predict psychological empowerment, and indirectly influence positive academic emotions through psychological empowerment. The relationship between perceived formative evaluation and learning autonomy was partially mediated by the chain of psychological empowerment and positive academic emotions. The findings indicate that perceived formative evaluation could enhance the psychological empowerment of medical students for their academic learning, and promote positive academic emotions through psychological empowerment, further encourage learning autonomy. This study highlights the importance of both psychological empowerment and positive academic emotions aspect of learning to optimize educational outcomes, offering insights into the design of effective educational evaluations that can facilitate learning autonomy and empower students in medical education.